Pola Komunikasi Anak Perempuan Tionghoa di Kota Dumai dalam Struktur Keluarga Patriarki - Chalvin Weslee; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Communication discrimination frequently occurs in Chinese ethnic families thatcontinue to perpetuate a patriarchal system. This study aims to examine the forms ofcommunication discrimination and analyze the communication patterns of Chinesedaughters dominated by a patriarchal family structure. This research employs a qualitativemethod with an ethnographic approach. Data collection was conducted through semistructuredin-depth interviews with five daughters of Chinese descent. Data analysisutilized thematic analysis to interpret patterns of meaning. The results indicate thatcommunication discrimination manifests through epistemic injustice and symbolic violence,where the voices and capacities of daughters are underestimated due to gender bias. Theresulting communication pattern operates within a high power distance structure,rendering the father's authority absolute and indisputable. In response to this repression,daughters employ self-silencing strategies to avoid conflict and practice covert resistance.It is concluded that these gender-biased cultural practices place daughters in a subordinateposition that silences their agency, highlighting the need for reconstruction towards anegalitarian family communication pattern.